The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/aem.70.2.693-703.2004
|View full text |Cite
|
Sign up to set email alerts
|

NorM, an Erwinia amylovora Multidrug Efflux Pump Involved in In Vitro Competition with Other Epiphytic Bacteria

Abstract: Blossoms are important sites of infection for Erwinia amylovora, the causal agent of fire blight of rosaceous plants. Before entering the tissue, the pathogen colonizes the stigmatic surface and has to compete for space and nutrient resources within the epiphytic community. Several epiphytes are capable of synthesizing antibiotics with which they antagonize phytopathogenic bacteria. Here, we report that a multidrug efflux transporter, designated NorM, of E. amylovora confers tolerance to the toxin(s) produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 60 publications
0
50
0
2
Order By: Relevance
“…Similarly, expression of Burkholderia vietnamiensis NorM in an E. coli acrAB mutant strain complemented its hypersensitivity to norfloxacin (11). Thus, H. pylori HP1184 encodes a NorM homolog that actively extrudes ethidium bromide in vitro, similar to the homolog found in other bacteria (7,11,20). However, the H. pylori HP1184-knockout mutant was not more susceptible to norfloxacin, indicating a difference in substrate specificity.…”
Section: Efflux Systems Have Been Identified In Hmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, expression of Burkholderia vietnamiensis NorM in an E. coli acrAB mutant strain complemented its hypersensitivity to norfloxacin (11). Thus, H. pylori HP1184 encodes a NorM homolog that actively extrudes ethidium bromide in vitro, similar to the homolog found in other bacteria (7,11,20). However, the H. pylori HP1184-knockout mutant was not more susceptible to norfloxacin, indicating a difference in substrate specificity.…”
Section: Efflux Systems Have Been Identified In Hmentioning
confidence: 80%
“…Transformation of a hypersensitive E. coli strain with V. parahaemolyticus norM conferred resistance to norfloxacin and ethidium bromide, and elevated efflux of ethidium bromide was observed (20). In Erwinia amylovora NorM mediates resistance to hydrophobic cationic compounds like norfloxacin and ethidium bromide (7). Similarly, expression of Burkholderia vietnamiensis NorM in an E. coli acrAB mutant strain complemented its hypersensitivity to norfloxacin (11).…”
Section: Efflux Systems Have Been Identified In Hmentioning
confidence: 99%
“…sepedonicus, which forms bacterial aggregates embedded in an exopolymetric matrix and attaches to the walls of xylem vessels of potato plants (7,28). Colonization of the xylem vessels is also central in the systemic spread of gram-negative phytopathogens such as Erwinia amylovora (4,26). Furthermore, D. solani, a member of the SRE, has also been shown to utilize xylem vessels to systemically colonize potato plant tissues following root, stem, and leaf infection.…”
Section: Discussionmentioning
confidence: 99%
“…brasiliense 1692 and P. carotovorum subsp. brasiliense mCherry strains were prepared in LB broth and grown to a cell density of an optical density at 600 nm (OD 600 ) = 1 (≈1 × 10 8 CFU/ml), washed, and resuspended in 10 mM MgSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Many multidrug efflux pumps in Gram-negative bacteria like E. coli, K. pneumoniae, and E. cloacae are controlled by special regulatory systems that mediate responses to hostile environments (37). In addition, studies of Gram-negative efflux pumps revealed that the expression of several transporters of the RND (resistance-nodulation-division) family of multidrug (MDR) transporters were induced by and transported cellular metabolites as part of the bacterial cell physiology (38)(39)(40). Since Tet38 conferred resistance to fatty acids, a natural host defense component, we observed the effects of certain lipids on the gene expression levels of tet38 and its regulators tetR21 and mgrA.…”
Section: Discussionmentioning
confidence: 99%